Chemical weed control in direct-seeded rice using drone and mist flow spray technology - Abd Ghani, Muhd Azlan; Juraimi, Abdul Shukor; Mat Su, Ahmad Suhaizi; Ahmad-Hamdani, Muhammad Saiful; Islam, A.K.M. Mominul; Motmainna, Mst (Elsevier, 2024)
Weeds are the primary pest that reduces crop yield. Herbicide-based weed control is an efficient strategy for farmers, offering economically feasible weed management for agricultural crop production. The effectiveness of agrochemicals relies on the correct calibration and exact calculations of the rates needed per unit area, uniform distribution over treated surface and spraying conditions. The current investigation aims to investigate the efficacy of selected herbicides for weed control using drones. A field experiment was carried out in a commercial plot in Sungai Besar, Sabak Bernam Selangor, from September to December 2022 and April to July 2023 to assess the effectiveness of using drones to apply herbicides in direct-seeded rice. The main goal was to assess the effectiveness of Rinskor (Loyant), Rinskor + Cyhalofop (Novlect), Cyhalofop (Clincher), Bispyribac (Nominee), and Propanil (Stam 80WG) herbicides in suppressing weeds in direct-seeded rice using drone and mist blower sprayers, as well as their operational efficiency. The experimental plot was arranged using a randomized complete block design with three replications. The results of the experiments recorded the toxicity of the herbicides on rice at early stage but rice plant was recovered at 21 days after spray. High grain yield components were recorded for the Novlect and Loyant treated plots. The density and dry weight of grasses, sedges, and broad-leaved weeds were considerably reduced when the herbicides were applied using mist blowers and drones. Nominee showed the lowest weed control efficiency compared to other applied herbicides in both seasons. Results showed that compared to the mist blower application, applying Novlect via drone is more successful for timely weed control in direct-seeded rice, which in turn reduces labor intensity and hardship.